PENGEMBANAN MEDIA PEMBELAJARAN PADA MATERI BERFIKIR KOMPUTASIONAL KELAS X DI SMK DEK PADANG - Niken Danel Putri; Adlia Alfiriani; Mourend Devegi (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2023)
The purpose of this study is to produce learning materials for computer science subjects at the DEK Padang (BK) School of Professional Computer Thought. This study uses research and development methods. The development model used in this study is the ADDIE model. The object of research used is the classroom. The search engine is a valuable tool because it uses a questionnaire that is validated by 6 validators. The authentication process includes 3 media authenticators and 3 hardware authenticators. The current instrument used a questionnaire administered to 24 students and 3 educators. The product created in this research is a learning tool. Based on the vehicle validation results, a vehicle validation score of 82.22 was achieved in the “Very valid” category. The result has a significant value of 90.97 with the category “Very valid”. We can therefore conclude that learning media is “very valuable”. Based on task results, educators received a score of 91.74 in the “Very Realistic” category. The student's practice level is 81.05 at the "Very Practical" level.